PENGARUH KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PELANGGAN DI TOKO DISTORTION MERCH MALANG. - Ahmad Prayogi Wicaksono; N. Rachma; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABTRACTThis study aims to find the effect of customer satisfaction on buying interest in Distortion Merch Products in Malang. The study uses primary and secondary data with seven specific reference variables for indicators that are applied to interest in repurchasing and customer satisfaction. The analysis used is simple linear analysis with 100 respondents who made twice purchases at Distortion Merch in Malang. The results of this study state that there is a significant effect between customer satisfaction and interest in repurchasing, the effect of customer satisfaction on the interest in repurchasing customers in the Distortion Merch Shop Malang is 67.7%. While 32.3% interest in repurchasing customers is influenced by other variables not included in this study. This study shows that customer satisfaction in Malang Distortion Merch affects the interest in repurchasing and customer satisfaction itself..Keywords: customer satisfaction, Repurchase Interest